Asparagine deprivation mediated by Salmonella asparaginase causes suppression of activation-induced T cell metabolic reprogramming. Issue 2 (23rd October 2015) - Torres, AnnMarie; Luke, Joanna D; Kullas, Amy L; Kapilashrami, Kanishk; Botbol, Yair; Koller, Antonius; Tonge, Peter J; Chen, Emily I; Macian, Fernando; van der Velden, Adrianus W M
Abstract : Asparagine deprivation causes inhibition of T cell activation characterized by the suppression of mTOR signaling, autophagy, Myc expression, and lactate secretion. Abstract: Salmonellae are pathogenic bacteria that induce immunosuppression by mechanisms that remain largely unknown. Previously, we showed that a putative type II l -asparaginase produced by Salmonella Typhimurium inhibits T cell responses and mediates virulence in a murine model of infection. Here, we report that this putative l -asparaginase exhibits l -asparagine hydrolase activity required for Salmonella Typhimurium to inhibit T cells. We show that l -asparagine is a nutrient important for T cell activation and that l -asparagine deprivation, such as that mediated by the Salmonella Typhimurium l -asparaginase, causes suppression of activation-induced mammalian target of rapamycin signaling, autophagy, Myc expression, and l -lactate secretion. We also show that l -asparagine deprivation mediated by the Salmonella Typhimurium l -asparaginase causes suppression of cellular processes and pathways involved in protein synthesis, metabolism, and immune response. Our results advance knowledge of a mechanism used by Salmonella Typhimurium to inhibit T cell responses and mediate virulence, and provide new insights into the prerequisites of T cell activation. We propose a model in which l -asparagine deprivation inhibits T cell exit from quiescence by causing suppression of activation-induced metabolic reprogramming.